PENGENALAN DAN PENGGUNAAN SOFTWARE KIMIA UNTUK SISWA SMAN 2 BENGKULU TENGAH - I Nyoman Candra; Elvinawati; Wiwit (Universitas Bengkulu, 2025)
Chemistry is one of the subjects that is still considered difficult and less interesting by most students, including those at SMAN 2 Bengkulu Tengah. The use of Chemistry Software has become one of the learning media solutions that can help students in learning chemistry. Therefore, an introduction to Chemistry Software was conducted for the students of SMAN 2 Bengkulu Tengah. This activity was carried out through an introduction and demonstration method and took place on September 26, 2025. Based on the results of the satisfaction questionnaire distributed, the majority of participants stated that the implementation of the introduction and use of Chemistry Software was interesting (74%) and very interesting (21%). In addition, the participants felt more motivated to learn chemistry and hoped that similar activities could be held again. Overall, this activity ran smoothly and was enthusiastically participated in by the students. Keywords: Avogadro; IqMol; Computational Chemistry; HyperChem